The Role of Extracellular Matrix Components in the Spreading of Pathological Protein Aggregates - Moretto, Edoardo; Stuart, Skye; Surana, Sunaina; Vargas, Jose Norberto S.; Schiavo, Giampietro (Frontiers in Cellular Neuroscience, 2022)
Several neurodegenerative diseases are characterised by the accumulation of aggregated misfolded proteins. These pathological agents have been suggested to propagate in the brain via mechanisms similar to that observed for the prion protein, where a misfolded variant is transferred from an affected brain region to a healthy one, inducing the misfolding and/or aggregation of correctly folded copies. This process has been characterised for several proteins, such as α-synuclein, tau, amyloid beta (Aβ) and less extensively for huntingtin and TDP-43. α-synuclein, tau, TDP-43 and huntingtin are intracellular proteins, and their aggregates are located in the cytosol or nucleus of neurons. They have been shown to spread between cells and this event occurs, at least partially, via secretion of these proteins in the extracellular space followed by re-uptake. Conversely, Aβ aggregates are found mainly extracellularly, and its spreading occurs in the extracellular space between brain regions. Due to the inherent nature of their spreading modalities, these proteins are exposed to components of the extracellular matrix (ECM) including glycans, proteases and core matrix proteins. These ECM components can interact with or process pathological misfolded proteins, potentially changing their properties and thus regulating their spreading capabilities. Here, we present an overview of the documented roles of ECM components in the spreading of pathological protein aggregates in neurodegenerative diseases with the objective to identify the current knowledge gaps and stimulate further research in the field. This could potentially lead to the identification of druggable targets to slow down the spreading and/or progression of these pathologies.